KENDALA PENGUKURAN PANJANG BADAN, BERAT BADAN, DAN LINGKAR LENGAN ATAS PADA BALITA DI POSYANDU SOKON, FATUKOA - Umbu Djama Landutana; Teresha Julia Yunita Alastan; Yunita Astari Karambe; Regina Marvina Hutasoit (Jurnal Media Tropika, 2023)
The toddler period is the first year of human life. This period is an important and critical period. The toddler period is classified as a developmental stage that has the potential to have health problems because the immune system in toddlers is not strong enough to deal with viruses or germs from outside. In this regard, it is necessary to monitor nutritional status by measuring physical growth using anthropometric parameters. Monitoring of nutritional status that is often carried out regularly at posyandu is measuring body length (PB), body weight (BB) and upper arm circumference (LILA). During the measurement activities at Posyandu Sokon, Fatukoa, difficulties and challenges were found that could bias the measurement, so it is very important to handle and control it so that the results obtained are valid and do not harm the clients being served. The tool used to measure body length is the Length Board, for body weight is a digital scale, and to measure the LILA uses the LILA tape. The number of toddlers measured was 63 people. From the inspection activities, there were many obstacles when taking measurements where the most common difficulties were found, namely toddlers who often cry and cannot be silent when they want to be examined